Placental measurements and their association with birth weight in a Brazilian cohort - Lígia Moschen de Paula Nascente; Carlos Grandi; Davi Casale Aragon; Viviane Cunha Cardoso (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2020)
ABSTRACT: Introduction: Epidemiological studies have shown associations between placental measurements and perinatal and later life outcomes. Objectives: To report placental measurements and evaluate their association with birth weight in a Brazilian birth cohort. Methods: Retrospective cohort study with 958 mothers, placentas, and newborns delivered at the Ribeirão Preto Medical School Hospital, Universidade de São Paulo, Brazil, in 2010 and 2011. The information was collected from interviews, medical records, and pathology reports. The placental measurements were: weight, largest and smallest diameters, eccentricity, thickness, shape, area, and birth weight/placental weight and placental weight/birth weight ratios. We analyzed the associations between birth weight and placental measurements using multiple linear regression. Results: Placental weight alone accounted for 48% of birth weight variability (p < 0.001), whereas placental measurements combined (placental weight, largest and smallest diameters, and thickness) were responsible for 50% (p < 0.001). When adjusted for maternal and neonatal characteristics, placental measurements explained 74% of birth weight variability (p < 0.001). Conclusion: Placental measurements are powerful independent predictors of birth weight. Placental weight is the most predictive of them, followed by the smallest diameter.